The Effect of Profitability Ratios and Liquidity Ratios on Share Prices of Companies in the Consumer Goods Sector Listed on the Indonesian Stock Exchange for the 2016-2021 Period - Mustofa Rahmadhani; Tiar Lina Sutingkir (Primanomics : Jurnal Ekonomi & Bisnis, 2023)
The purpose of this research is to describe the profitability ratio, liquidity ratio, and stock price, as well as to ascertain whether the current ratio, return on equity, and return on assets have any partial or simultaneous effects on stock prices. In this study, a quantitative strategy is combined with a descriptive verification method. This study's objectives include describing the profitability ratio, liquidity ratio, and stock price, as well as evaluating return on equity and return on assets' effects Using data from 60 financial reports, six years of observation were used. The findings demonstrate that both the return on equity and the return on assets In the data analysis procedure, multiple linear regression analysis and hypothesis testing are performed. The population of the study consists of the 76 consumer products businesses that are traded on the Indonesian stock exchange. Using a deliberate sampling strategy, 10 companies were found. This study's objectives include describing the profitability ratio, liquidity ratio, and stock price, as well as evaluating return on equity and return on assets' effects Six years of monitoring are used, yielding 60 financial report data. The findings indicate that while the current ratio has an impact on stock prices, return on assets and return on equity have a little impact. Return on assets, return on equity, and current ratio significantly influence stock prices of consumer products businesses listed on the Indonesia Stock Exchange between 2016 and 2021.